From profit to prosperity? The role of corporate communication in sustainability - Eiró-Gomes, Mafalda (2019)
For many years the triple bottom line while speaking about corporations success can be said to be summarized in three words: people, planet and profit. We are, as you may easily understand, speaking about what is in general cited in manuals as questions concerning the social, environmental and economical sustainability of organizations. As with some other concepts the notion of corporate social responsibility does not have either a consensual definition or unanimous empirical applications. In the last decade a set of concepts has emerged as umbrella concepts for a series of policies and practices that organizations tend to promote and that can be seen as going beyond strictly legal aspects, and envisage the public good. The authors are thinking about concepts as those of philanthropy, enterprise responsibility (much more common in french speaking organizations) corporate responsibility, corporate social responsibility, that for many are interchangeable with that of corporate citizenship (Broom and Sha, 2013). In these paper, and even if the authors disagree with the perspective that considers all the concepts as equivalent, this will not be an issue under discussion. The concept of Corporate Social Responsibility (CSR) will be the one used here due to the fact that the organizations under analysis belong to a portuguese non-for profit association that has as its mission to promote corporate social responsibility as well as to enhance the reflection on these issues (GRACE) this will be the core designation used in this paper. It might be important to note too that CSR is the designation cited by the great majority of the organizations interviewed as naming these kind of policies or the departments when existing. The concept of CSR must be understood however as a very broad notion and in a quite wittgensteinian way, that is, in the sense of family resemblance (Wittgenstein, 1953). Maybe as in no other context this is a proficuous idea. No one seems to be able to offer an univocal definition of these policies or practices, many organizations understand their responsibilities towards society in quite divergent ways but all the tentatives to clarify or even regulamentar these approaches don't seem to have had great success, or at least don't seem to be able to cover all the spectrum of interpretations and initiatives. The international certifications and regulations, as the GRI (global reporting initiative) even if very useful in enabling global indicators to compare the work of different organizations towards economic, environmental and social impacts don't mirror the diversity of approaches and understanding of these issues. Curiously however even the GRI is promoting a much more inclusive use of the concept of "sustainability" as can be well visible by its adoption of the phrase "empowering sustainable decisions" as the GRI signature the motto that summarizes its mission. And this was precisely one of the main goals of this research. How do organizations that consider themselves worried with these questions tend to understand them? How do they interpret their responsibilities towards the public good and the planet? What is, and what do the organizations think it will be, the main role of the communication professionals in a near future in the development and implementation of better and more responsible policies, practices and it goes without saying reporting them?